Probiotics and food allergy [Probiyotikler ve besin alerjisi] - (:unkn) unknown (My University, 2005)
Atopic diseases such as atopic eczema, allergic rhinitis, asthma and food allergy constitute a matter of increasing importance in developed countries, while genetic factors fail to explain the rapid rise in the incidence of the disease. The first rule in the treatment of allergies to specific foods involves the removal of the allergen from the diet, thereby decreasing the humoral and cellular immune responses. However, as elimination therapies lead to insufficient nourishment due to allergies to vitally important foods, the need for new novel approaches have arised for the management of food allergies. Probiotics, whose importance was stressed one hundred years ago, are live non-pathogenic microbial feed supplements which beneficially affect the host animal by improving its microbial balance. The role of probiotics in the treatment of food allergies is explained by an extension of the "hygiene hypothesis" suggested by Strachan a decade ago. This hypothesis holds that the growing prevalance of allergic diseases in western societies is in part due to our increasingly sterile surroundings accompanying modern life style. The increasing consumption of processed and industrial foods leads to insufficent stimulation of the infant's immune system. The function of probiotics in the management of food allergies aims to strengthen the immunologic and non-immunologic barriers, thus steering the infant's immune system away from the tendency to overreact to normally benign substances (tolerance), while forming the ability to develop an inflammatory response to potential pathogens.